Formulation and In Vitro Evaluation Mirtazapine Oral Disintegrating Tablets by Sublimation Method - Snigdhanjani, Mora Sri (International Journal of Pharmaceutical & Biological Archive, 2021)
For the past one decade, there has been an enhanced demand for more patient friendly and compliant dosage forms. As a result, the demand for developing new technologies has been increasing annually. Since the development cost of a new drug molecule is very high, efforts are now being made by pharmaceutical companies to focus on the development of new drug dosage forms for existing drugs with improved safety and efficacy together with reduced dosing frequency, and the production of more cost-effective dosage forms. For most therapeutic agents used to produce systemic effects, the oral route still represents the preferred way of administration, due to its several advantages and high patient compliance compared to many other routes. Mirtazapine is a tetracyclic piperazino-azepine antidepressant agent that was initially approved for the treatment of major depressive disorder in the Netherlands in 1994. Drug and excipient compatibility was confirmed by comparing spectra of Fourier transform infrared analysis of pure drug with that of various excipients used in the formulation. The results of the drug-excipient compatibility studies revealed that there was no chemical interaction between the pure drug and excipients.